2013
DOI: 10.1155/2013/792413
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Goiter Associated with Amyloidosis Secondary to Rheumatoid Arthritis

Abstract: Amyloidosis refers to a variety of conditions in which amyloid proteins are abnormally deposited in organs and/or tissues. The most common forms of systemic amyloidosis are primary amyloidosis (PA) of light chains and secondary amyloidosis (SA) caused by chronic inflammatory diseases such as rheumatoid arthritis (RA). Although involvement of the thyroid gland by amyloid is a relatively common phenomenon, clinically significant enlargement of the thyroid owing to amyloid deposition is a rare occurrence. In SA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Two other reports describe amyloid goiters with diffuse infiltration by adipose tissue (14, 15). The authors attribute the increase in size to amyloid deposits – in spite of the infiltration by fat – which underscores the lack of clear criteria to differentiate thyroid lipomatosis with amyloid deposits from amyloid goiters with fat infiltration.…”
Section: Discussionmentioning
confidence: 93%
“…Two other reports describe amyloid goiters with diffuse infiltration by adipose tissue (14, 15). The authors attribute the increase in size to amyloid deposits – in spite of the infiltration by fat – which underscores the lack of clear criteria to differentiate thyroid lipomatosis with amyloid deposits from amyloid goiters with fat infiltration.…”
Section: Discussionmentioning
confidence: 93%
“…Some of the published cases have reported massively enlarged thyroids with masses of 500-700 g [7]. e usual treatment is total thyroidectomy [3], performed in our case and in the 9 cases mentioned, necessary both to relieve symptoms and to establish the definitive diagnosis. Preoperatory suspicion is important if there are long-standing co-morbidities, including confirmed amyloidiosis, because it is useful to guide the surgeon, due to the risk of local extension and differential diagnosis with a thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 73%
“…Until 2000, García-Villanueva et al referred 200-250 published cases [5]. In our review, we have only found 9 cases published in the last 10 years, all of them were associated with kidney disease (CKD), with or without kidney transplant: 3 of them were associated with familial Mediterranean fever [1,6], 2 cases were associated with rheumatoid arthritis [3,7], 1 case was associated with bronchiectasis [2], another case with bronchiectasis and ankylosing spondylitis [1], and other 2 cases were associated with Crohn's disease [4] and multiple myeloma [8] ( Table 1). Hijazi et al [9] reviewed four more cases of thyrolipomatosis until 2018, publishing a new case in a 53-year-old woman with renal failure secondary to diabetic nephropathy, without anatomopathological study for amyloid.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…6266 Amyloidosis may cause dysmotility, and has been associated with goiter leading to extrinsic esophageal compression. 6769…”
Section: The Gi Tract In Ra Pathogenesismentioning
confidence: 99%